Giant Congenital Melanocytic Nevi Successfully Treated with Combined Laser Therapy - Sakhiya, Jagdish (Indian Dermatol Online J, 2020)
Congenital melanocytic nevi are benign proliferations of cutaneous melanocytes that arise as a result of abnormal growth, development, or migration of melanoblasts. Clinically, the giant congenital nevus is greater than 20 cm in size, pigmented and often hairy. The risk of malignant melanoma for the giant nevi is almost 6%. Fifty percent of the melanomas develop by the age of 2 years and, 80% of the melanomas develop by the age of 7 years. Hence, early management is of paramount importance. Herein, we present a case of giant nevi along with a review of the literature in order to bring awareness among clinicians towards this rare albeit significant entity.